Controversies of cryptocurrency: Fatwa analysis and implications from Muhammadiyah and NU perspectives in Indonesia - Munandar, Siswoyo Aris; Fahrurrozi, Fahrurrozi (Journal of Islamic Law on Digital Economy and Business, 2025)
Purpose – This study aims to analyze the controversy surrounding cryptocurrency from the perspectives of Muhammadiyah and Nahdlatul Ulama (NU), focusing on their respective fatwas, the underlying juridical argumentation, and the social and economic implications of these religious rulings in Indonesia. Methodology – Employing a qualitative normative legal approach, the research conducts a comprehensive document analysis of official fatwas issued by Muhammadiyah and NU, complemented by secondary sources such as academic articles, news reports, and government regulations related to cryptocurrency in Indonesia. Findings – Both Muhammadiyah and NU consistently declare crypto-currencies haram (forbidden) primarily because of Islamic legal principles prohibiting gharar (excessive uncertainty), maisir (gambling), and the lack of state sanctions and consumer protection. While sharing this conclusion, the two organizations differ in their juridical methodologies, with NU exhibiting more contextual flexibility through internal debates and regional councils. Implications – The fatwas serves as authoritative guidance shaping Muslim consumer choices and government regulations, reinforcing Islamic ethical standards in financial transactions. However, they also create tension between technological innovation and religious compliance, posing challenges to fintech adoption and inclusive economic growth. The findings suggest the need for ongoing dialogue between scholars, regulators, and industry stakeholders to reconcile Sharia compliance with digital financial innovation. Originality – This study provides an original contribution by offering a comparative, in-depth analysis of the legal reasoning within the Muhammadiyah and NU fatwas on cryptocurrency, linking doctrinal argumentation to broader socioeconomic outcomes. It fills a gap in the existing literature that mostly catalogs fatwa content without examining their interpretive nuances and practical impacts in Indonesia’s unique socio-religious context.